CircRNAs as Novel Biomarkers and Therapeutic Targets in Renal Cell Carcinoma - Zhou, Yuxia; Li, Cheng; Wang, Zhenping; Tan, Shuangfeng; Liu, Yiqi; Zhang, Hu; Li, Xuefeng (Frontiers in Molecular Biosciences, 2022)
Circular RNAs (circRNAs) are a type of long non-coding RNA with covalently closed loops that are naturally resistant to exoribonuclease. With the rapid development of high-throughput sequencing technologies and bioinformatics, increasing data suggest that circRNAs are abnormally expressed in renal cell carcinoma (RCC) and act as important regulators of RCC carcinogenesis and progression. CircRNAs play important biological roles in modulating cell proliferation, migration, invasion, apoptosis, and gemcitabine chemoresistance in RCC. Most of the circRNAs studied in RCC have been reported to be significantly associated with many clinicopathologic characteristics and survival parameters of RCC. The stability and specificity of circRNAs enable them potential molecular markers for RCC diagnosis and prognosis. Moreover, circRNAs have emerged as targets for developing new therapies, because they can regulate various signaling pathways associated with RCC initiation and progression. In this review, we briefly summarize the biogenesis, degradation, and biological functions of circRNAs as well as the potential clinical applications of these molecules for RCC diagnosis, prognosis, and targeted therapy.